Limb salvage surgery of primary and metastatic bone tumors of the lower extremity: Functional outcomes and survivorship of modular endoprosthetic reconstruction - EROL, BÜLENT; ŞİRİN, EVRİM; TOPKAR, OSMAN MERT (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2021)
Objective: The study was aimed to determine the survivorship and functional outcomes of modular endoprosthetic reconstruction in the management of primary and metastatic bone tumors of the lower limbs and to investigate the rate and causes of implant failure. Methods: A total of 84 limbs of 82 patients (49 male, 33 female; mean age=48 years, age range=13-78 years) with a minimum follow-up of 12 months in whom resection and modular endoprosthetic reconstructions were performed for primary or metastatic bone tumors of the lower extremity were retrospectively reviewed and included in the study. The mean follow-up was 43 (range=13-119) months. Functional status was assessed using the Musculoskeletal Tumor Society (MSTS) scoring system at the final follow-up. Implant survival was defined as the time from implantation until partial or complete exchange of the prosthesis secondary to mechanical or nonmechanical causes or amputation. The effects of the anatomical site on functional scores and implant survival were statistically analyzed. Additionally, the effects of diagnosis and adjuvant treatments on functional scores, implant survival, and failure rates were investigated. Results: At the time of the study, 55 patients were still alive with a mean follow-up of 48 (range=15-119) months. The mean MSTS scores resulting from the final follow-up of all patients and of those surviving were 87.9% (range=16%-100%) and 86.8% (range=16%-100%), respectively. Overall implant survival was 95.2%, 89.2%, 87%, and 87% at 1, 2, 3, and 4 years, respectively. Statistically, both functional scores and implant survival analysis in different anatomical sites were found similar. In 15 of the patients (17.8%), endoprosthetic reconstructions had failed. The causes of failure were soft tissue failure (dislocation) in 5 patients, infection in 5, structural/mechanical failure in 2, local recurrence in two, and aseptic loosening in one. The diagnosis and receiving preoperative and/or postoperative adjuvant treatment did not affect functional scores, implant survival or failure rates. Conclusion: The results of this study have shown that modular endoprosthetic replacement can provide satisfactory functional results and a durable mid-term limb salvage option in the management of patients with primary and metastatic bone tumors of the lower limbs.
Keywords: Limb salvage surgery; Modular endoprosthetic reconstruction; Lower extremity; Bone sarcomas; Metastatic bone tumors; EXTRACORPOREAL IRRADIATION; REPLACEMENT; CLASSIFICATION; RESECTION; DISEASE; FEMUR